2022
DOI: 10.1049/itr2.12156
|View full text |Cite
|
Sign up to set email alerts
|

Path tracking control for autonomous vehicles with saturated input: A fuzzy fixed‐time learning control approach

Abstract: This paper presents a fuzzy fixed‐time learning path tracking control strategy for autonomous vehicles with saturated input and uncertainties. First, Takagi‐Sugeno (T‐S) model is designed to realize an accurate description of the nonlinear path tracking systems. The T‐S model is the weighted sum of a series of linear dynamics models. The weighting coefficients are described by fuzzy membership functions. Then, with the consideration of the saturated input, a fixed‐time learning control is proposed. It contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…From another perspective, the convergence performance of a controlled system is characterized by the settling time [17], and achieving fast convergence is often desirable in practice. The settling time property can be classified into asymptotic, finite-time, and fixed-time convergences.…”
Section: Introductionmentioning
confidence: 99%
“…From another perspective, the convergence performance of a controlled system is characterized by the settling time [17], and achieving fast convergence is often desirable in practice. The settling time property can be classified into asymptotic, finite-time, and fixed-time convergences.…”
Section: Introductionmentioning
confidence: 99%
“…The actuator nonlinearities such as backlash, deadzone, and saturation can degrade the path following performance or even lead to instability of the control system [50][51][52]. Several studies have reported the path tracking control of AGV subjected to input saturation [53][54][55][56][57][58][59][60][61]. The authors in [62,63] studied the steering control of AGV with input backlash.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some scholars have adopted several intelligent optimisation algorithms. Aiming at the uncertain and saturated input factors of autonomous vehicles, a fuzzy fixed-time learning path-following control strategy is proposed 20 in this study, but the fuzzy membership function continues to require human experience for selection. Carlucho et al 21 presented an incremental Q-learning mobile robot control strategy with adaptive PID control, which can be applied to the real environment under variable conditions.…”
Section: Introductionmentioning
confidence: 99%